The effect of decision training on anticipation and creative decision-making in badminton - Maryam Khalaji; Parvaneh Shamsipour dehkordi; Fahimieh Ayadi; Faezeh Khoshdoni Farahani (University of Tehran, 2024)
Introduction: One of the most complex processes in the field of sports expertise is decision-making. In this respect, this study aimed to investigate the effect of decision training on anticipation and creative decision-making in badminton.Methods: The current research is a quasi-experimental type with a pre-test and post-test design. The statistical population of the present study was all female students aged 20 to 30 years, from which 40 female students were selected by the available sampling method and randomly assigned into two decision training and control groups. A creative decision-making questionnaire, video camera, laptop, and projector were the tools used in the research. In the pretest, creative decision-making and anticipation were measured with 20 video clips while watching a badminton overhead shot through a video clip that was interrupted at the moment of racket-ball contact. The training group practiced 400 decision training trials and the control group just recognized the direction of the shots. A post-test was taken after 48 hours.Results: The result revealed that in the post-test, the decision training group had more creativity in decision-making than the control group (F=2.64) and in the training group, the skill of anticipating the direction of the shots was better than the control group (F=4.17).Conclusion: According to the results, the decision training made the players of the training group recognize the direction and landing place of the shot with more creativity and provide several solutions for each shot. It seems that decision training has a significant effect in facilitating and providing different solutions.